Nutrition and oral health in sport: Time for action - Needleman, I.; Ashley, P.; Fairbrother, T.; Fine, P.; Gallagher, J.; Kings, D.; Maughan, R. J.; Melin, A. K.; Naylor, M. (British Journal of Sports Medicine, 2018)
What is the problem? Elite athletes have poor oral health, common negative self-reported performance effects and a lifelong burden for disease management.1-3 One central determinant of oral health is nutrition and in particular the consumption of dietary sugars, acidic food and drinks and eating behaviours. However, nutrition is also clearly of major importance in managing and improving athlete performance. Therefore, this call to action is to recommend strategies to prevent or mitigate the risk from nutrition to the short-term health and performance of athletes and to the long-term oral health of all active individuals. The target audience includes athletes, health professionals (nutritionists and dieticians, sport and exercise medicine practitioners, dental professionals), scientists in related fields, sport policy organisations and industry.